Properties study of cotton stalk fiber/gypsum composite - Li, G.; Yu, Y.; Zhao, Z.; Li, J.; Li, C.
This manuscript addresses treating cotton stalk fiber surface with styrene acrylic emulsion, which improves the interfacial combined state of cotton stalk fiber/gypsum composite effectively and improves its mechanical properties notably. Mixes less slag, ordinary Portland cement, etc., to modify gypsum base. The electron microscope was utilized to analyze and research on the effect on composite properties of the abovementioned mixtures.
Keywords: COTTON STALK FIBER; GYPSUM; COMPOSITE; INTERFACE; SEM